An experimental study to evaluate musculoskeletal disorders and postural stress of female craftworkers adopting different sitting postures. Issue 2 (2nd April 2016) - Maity, Payel; De, Sujaya; Pal, Amitava; Dhara, Prakash C.
Abstract : This study aimed to evaluate musculoskeletal disorders (MSDs) and postural stress among female craftworkers. The study was carried out on 75 adult female craftworkers in different districts of West Bengal. The prevalence of MSDs, body part discomfort (BPD) rating and body joint angles of the workers were evaluated with standard methods. Electromyography (EMG) of the shoulder and back muscles was recorded with the BIOPAC system. The prevalence of MSDs, BPD rating and deviation of joint angle were comparatively lower in the case of sitting on the floor with folded legs than squatting and sitting on the floor with stretched legs postures. The EMG and rms values of the shoulder and back muscles were comparatively lower in this posture. Therefore, it was concluded that sitting on the floor with folded legs was less hazardous and it imposed less postural stress in comparison to other sitting postures.